Enhancing Patient Care Through Structured Assessment Of Supracondylar Fractures: A Quality Improvement Project At Holy Family Hospital, Rawalpindi Medical University - Hira Waris; Rahman Rasool Akhtar; Riaz Ahmed; Muhammad Haider; Mohammad Mohsin Javaid; Waqas Ali (Journal of Rawalpindi Medical College)
Objective: Aim of this QIP is to investigate the neurovascular status documentation of supracondylar fractures in pediatric population and to devise and implement a new assessment proforma for evaluation of these fractures.